2006
DOI: 10.1057/palgrave.jibs.8400202
|View full text |Cite
|
Sign up to set email alerts
|

A quarter century of Culture's Consequences: a review of empirical research incorporating Hofstede's cultural values framework

Abstract: Since Geert Hofstede's Culture's Consequences: International Differences in Work-Related Values (Sage, 1980) was published, researchers have utilized Hofstede's cultural values framework in a wide variety of empirical studies. We review 180 studies published in 40 business and psychology journals and two international annual volumes between 1980 and June 2002 to consolidate what is empirically verifiable about Hofstede's cultural values framework. We discuss limitations in the Hofstede-inspired research and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,305
2
33

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,737 publications
(1,380 citation statements)
references
References 249 publications
(344 reference statements)
40
1,305
2
33
Order By: Relevance
“…Research on the relationship between PD and devolution of HRM is limited: Joiner (2001) noted that in high PD cultures, management is less likely to decentralize authority as it creates confusion and anxiety; Kirkman, Lowe and Gibson (2006) indicated that centralization of decision-making is significantly higher in countries with high PD. Similarly, Daniels and Gregarus (2014) reported low PD as related to higher participation in decision-making and employee empowerment.…”
Section: Thusmentioning
confidence: 99%
“…Research on the relationship between PD and devolution of HRM is limited: Joiner (2001) noted that in high PD cultures, management is less likely to decentralize authority as it creates confusion and anxiety; Kirkman, Lowe and Gibson (2006) indicated that centralization of decision-making is significantly higher in countries with high PD. Similarly, Daniels and Gregarus (2014) reported low PD as related to higher participation in decision-making and employee empowerment.…”
Section: Thusmentioning
confidence: 99%
“…These five countries systematically vary according to the four cultural dimensions of Hofstede, ranging from 37 to 89 for individualism, from 14 to 95 form masculinity, from 35 to 70 for power distance and from 35 to 92 for uncertainty avoidance (see Table 1). We focus on Hofstede's dimensions rather than others, given evidence that it has had far greater impact (Kirkman et al, 2006). In addition, even if Hofstede's scores have been criticized for being outdated and collected in a specific context, recent meta-analysis (Taras et al, in press) and data (Ralston et al, in press) show that if country scores tend to converge over time, the relative position of our five countries is relatively stable.…”
Section: Samplementioning
confidence: 99%
“…Key topics, such as the multinational enterprise (MNE), internationalization, and cross-country activities, inevitably connect to culture as a broad context or specific factor that cannot be ignored (Leung, Bhagat, Buchan, Erez, & Gibson, 2005). Culture has been positioned as an antecedent, moderator, and mediator of strategic choices from entry form and mode, patterns of international expansion, cross-border knowledge transfer, to joint venture performance, entrepreneurship, and MNE corporate social responsibility, as well as leadership style, expatriate placement success, and a host of other individual-level outcomes (Kirkman, Lowe, & Gibson, 2006;Taras, Kirkman, & Steel, 2010a). More recently, researchers also began to consider culture as a dependent variable, influenced by business activities, especially in the context of cross-border merger and acquisitions and MNEs (Brannen & Salk, 2000;Caprar, 2011).…”
Section: Introductionmentioning
confidence: 99%